(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
Chemical compositions of fruit and leaves in Persica mira (Koehne) Kov. et Kostina during the vegetation season is studied. We identified that dynamics in accumulation of pectin and phenolic substances is similar to P. vulgaris Mill., while dynamics in accumulation of the ascorbic acid and organic (titric) acids differs from P. vulgaris. In P. mira, catechins and leuсoanthocyanidines are strongly accumulated in fruits; ascorbic acid, carotenoides, protopectins, flavonols are present in leaves.